2003
DOI: 10.1175/1525-7541(2003)004<1012:pmpeum>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Probable Maximum Precipitation Estimation Using Multifractals: Application in the Eastern United States

Abstract: Probable maximum precipitation (PMP) is the conceptual construct that defines the magnitude of extreme storms used in the design of dams and reservoirs. In this study, the value and utility of applying multifractal analysis techniques to systematically calculate physically meaningful estimates of maximum precipitation from observations in the eastern United States is assessed. The multifractal approach is advantageous because it provides a formal framework to infer the magnitude of extreme events independent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
70
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 34 publications
9
70
0
1
Order By: Relevance
“…2). As reported by Douglas and Barros (2003), the most common range values of q D extend between a little less than 2 and slightly more than 3. Other studies have found values of q D between 1.7 and 5 (Fraedrich and Larnder 1993;Labat et al 2002).…”
Section: Multifractal Analysis Of the Rainfall Datasupporting
confidence: 54%
“…2). As reported by Douglas and Barros (2003), the most common range values of q D extend between a little less than 2 and slightly more than 3. Other studies have found values of q D between 1.7 and 5 (Fraedrich and Larnder 1993;Labat et al 2002).…”
Section: Multifractal Analysis Of the Rainfall Datasupporting
confidence: 54%
“…Mandelbrot, 1977Mandelbrot, , 1982) deals with simple scaling, which means that such behaviour is determined by one parameter, called fractal dimension (e.g. Mandelbrot, 1977Mandelbrot, , 1982Feder, 1988;Falconer, 1990;Hastings and Sugihara, 1993). In defining (fractal) dimension the idea of measurement at scale δ is fundamental.…”
Section: Some Aspects Of Scaling Theoriesmentioning
confidence: 99%
“…This parameter can be obtained by the box-counting method (see e.g. Feder, 1988;Falconer, 1990;Hastings and Sugihara, 1993). In practical applications of this method, the D-dimensional space of the observations is covered with gradually-decreasing (it is common that the size is decreased gradually by a factor of 2), non-overlapping boxes of side δ.…”
Section: Some Aspects Of Scaling Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Extreme precipitation events have been increasing since the late 20th century in the mid-latitude and high-latitude land Atmospheric Research 157 (2015) 137-152 precipitation events have received worldwide attention due to their large-scale impacts (Alexander et al, 2006;Boccolari and Malmusi, 2013;Déqué, 2007;Douglas and Barros, 2003;Easterling et al, 2000;Fu et al, 2010;Fu et al, 2013;Goswami et al, 2006;Schmidli and Frei, 2005).…”
Section: Introductionmentioning
confidence: 99%